2018
DOI: 10.1556/2060.105.2018.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Allantoin improves histopathological evaluations in a rat model of gastritis

Abstract: Purpose Gastritis is found to be one of the most common gastrointestinal diseases worldwide. However, current therapeutic agents cause side effects, interaction, and recurrence. Allantoin has anti-inflammatory and wound healing properties. In this study, the therapeutic effect of allantoin has been assessed on the histopathological indices and gastric mucosal barrier of male rats. Methods Male rats were equally divided into control, ethanol-induced gastritis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…1) ((2,5-Dioxo-4-imidazolidinyl) urea) is a biologically active phytochemical extracted from the roots of Symphytum officinale (comfrey) native to Europe 6 . It possesses wound healing and tissue regeneration activities, besides renowned anti-oxidant, anti-inflammatory, pain reducing and gastroprotective effects that have been proved using a diversity of in vitro assay methods, in vivo animal models as well as clinical studies [7][8][9][10][11][12] .…”
Section: Formulation Optimization and Characterization Of Allantoin-loaded Chitosan Nanoparticles To Alleviate Ethanol-induced Gastric Ulmentioning
confidence: 99%
“…1) ((2,5-Dioxo-4-imidazolidinyl) urea) is a biologically active phytochemical extracted from the roots of Symphytum officinale (comfrey) native to Europe 6 . It possesses wound healing and tissue regeneration activities, besides renowned anti-oxidant, anti-inflammatory, pain reducing and gastroprotective effects that have been proved using a diversity of in vitro assay methods, in vivo animal models as well as clinical studies [7][8][9][10][11][12] .…”
Section: Formulation Optimization and Characterization Of Allantoin-loaded Chitosan Nanoparticles To Alleviate Ethanol-induced Gastric Ulmentioning
confidence: 99%
“…Studies have found that uric acid therapy is effective for ischemic stroke treatment ( Kand’ár et al., 2006 ; Llull et al., 2015 ). However, no stroke-related study has shown that allantoin has a similar effect to uric acid, but allantoin therapy has been used to treat other diseases, such as gastric ulcers ( da Silva et al., 2018 ) and gastritis ( Eslami-Farsani et al., 2018 ), which may offer a novel therapeutic opportunity for stroke. Therefore, further study is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of cellular metabolism, allantoin is found in a variety of organisms, from bacteria and plants, to invertebrates and vertebrates. The main therapeutic effects of allantoin (Figure 1) are stimulation of cell growth, regeneration of tissues and rebuilding of the granulation tissue [2][3][4][5][6][7]. Nutricosmetics are considered natural ingredients and products that act as nutritional supplements for the care of the beauty of hair, nails and skin, new innovative products being launched worldwide every year [4].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action involves stimulating fibroblast proliferation, elastin and collagen synthesis and the inhibition of the migration of inflammatory cells to the injury [11]. Recent studies have shown that allantoin has a beneficial effect in the treatment of gastritis [6], and it has also antihypertensive properties [12]. With a metformin-like chemical structure [13], both being guanidine derivatives, is has been proved that allantoin has a hypoglycemic effect [14].…”
Section: Introductionmentioning
confidence: 99%